Business processes analysis and redesign at Anglo-Chinese School (International) : Design and development of a Student Management System report. - Chin, Kah Shing. (2008)
To develop a new database design that allows proper management of students’ details and grades. The database should also allow report generating and analysis function from the collected students’ data.